New Water-Soluble Carbamate Ester Derivatives of Resveratrol - Andrea Mattarei; Massimo Carraro; Michele Azzolini; Cristina Paradisi; Mario Zoratti; Lucia Biasutto (Molecules, 2014)
Low bioavailability severely hinders exploitation of the biomedical potential of resveratrol. Extensive phase-II metabolism and poor water solubility contribute to lowering the concentrations of resveratrol in the bloodstream after oral administration. Prodrugs may provide a solution—protection of the phenolic functions hinders conjugative metabolism and can be exploited to modulate the physicochemical properties of the compound. We report here the synthesis and characterization of carbamate ester derivatives of resveratrol bearing on each nitrogen atom a methyl group and either a methoxy-poly(ethylene glycol)-350 (mPEG-350) or a butyl-glucosyl promoiety conferring high water solubility. Ex vivo absorption studies revealed that the butyl-glucosyl conjugate, unlike the mPEG-350 one, is able to permeate the intestinal wall. In vivo pharmacokinetics confirmed absorption after oral administration and showed that no hydrolysis of the carbamate groups takes place. Thus, sugar groups can be attached to resveratrol to obtain soluble derivatives maintaining to some degree the ability to permeate biomembranes, perhaps by facilitated or active transport.